PERKAWINAN ADAT MANDAILING DESA RABI JONGGOR KECAMATAN GUNUNG TULEH KABUPATEN PASAMAN BARAT (Studi Kasus Tradisi Manopot Kahanggi) - Syahru Romadon; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted in Rabi Jongor Village, Gunung Tuleh District, West Pasaman Regency. This study aims to determine the implementation of the manopot kahanggi tradition in traditional Mandailing marriages in Rabi Jonggor Village, as well as to find out whether there are changes in the implementation of the manopot kahanggi tradition in Mandailing traditional marriages in Rabi Jonggor Village. The theory used is the concept of the theory of the Mandailing and Manopot Kahanggi tribes. The sampling technique was purposive sampling. Researchers have prepared 4 research subjects and 1 key informant, namely the Adat King, and 4 people who have practiced the Manopot Kahanggi Tradition. Data analysis was performed using descriptive qualitative and data instruments were observation, interview and documentation. From the results of research in the field of Manopot Kahanggi Tradition, it is mandatory for prospective grooms to marry a woman from Rabi Jonggor Village, including the Marsapa Boru tradition; The Bond-Binding Tradition; and the Tradition of Giving Help. The Changes in the Implementation of the Manopot Kahanggi Tradition, including the Changes in the Implementation of Marsapa Boru; Change in the implementation of the binding; and Changes in the Implementation of Providing Assistance in accordance with the existing customary rules in the village. There are only changes in the time or day of its implementation, be it the tradition of Marsapa Boru, Ikat-Binding, and Giving Aid. KeyWords: Tradition, Marriage, Implamentation, Change